Analisis Pengaruh Perubahan Arus Kas, Laba Akuntansi dan Risiko Sistematika terhadap Return Saham - Bryan Genisius Rolando; Ratih Qadarti Anjilni (Jurnal Riset Akuntansi, 2025)
This research is motivated by the existence of a capital market that has experienced very good growth and development. The capital market has an important role in a country's economy so that the capital market has a significant impact on the country and the capital market has become a financial center. The purpose of this study is to test whether cash flow, accounting profit and systematic risk affect stock returns in food and beverage sub-sector companies. The data collection technique is a documentation technique. The research sample is a food and beverage sub-sector company listed in 2019-2023. The sampling technique uses purposive sampling, which is based on certain criteria so that 24 companies are obtained as research samples. The data used in this study are secondary data in the form of financial reports. Data analysis uses multiple regression analysis processed using the Econometric Views (EViews) program. The data analysis technique used in this study is panel data regression with a random effect model. The results of this research test indicate that cash flow, accounting profit and systematic risk simultaneously affect stock returns in food and beverage sub-sector companies. Partially, accounting profit has a significant effect on stock returns, while cash flow and systematic risk do not affect stock returns in food and beverage sub-sector companies.